Dampak pemanfaatan ICT dalam pendidikan - Saharuddin Saharuddin; Misita Anwar (Seminar Nasional LP2M UNM, 2019)
ICT has been considered a fundamental need in the world of education. All aspects of education cannot be separated from the support of ICT utilization. However, several studies have found that ICT has not had a significant impact in improving the quality of the education process. Some problems are often discussed, among others; 1) ICT understanding dichotomy as a tool. ICT is used as a tool not as an ultimate goal to be achieved. 2) ICT as a new area. In most cases, educators consider ICT as a new area (subject matter) not a new way of teaching and interaction with students. 3) Several phenomena in ICT among others; the impact of the use of ICT is not clear because of the absence of assessment indicators, very little data is obtained regarding ICT in education, ICT used in isolation is not integrated with other subjects and best practice is rarely disseminated so it does not have a broad impact.